Mengungkap Akuntansi Budaya Atas Pembiayaan Ritual Rambu Solo Suku Toraja - Zulfaidah, Zulfaidah; Riazavita, Efni (YUME : Journal of Management, 2024)
This study aims to determine the cultural accounting system in financing the rambu solo' ritual in the Toraja tribe, Lembang Belau, Masanda District. The techniques used in data collection are observation, interviews with traditional shops and families who carry out the rambu solo ceremony and also documentation. The results of the study indicate that the cultural accounting system in the rambu solo ritual in the Toraja tribe, Masanda District, starts from the sequence, agreement/decision making of financial transactions with the purchase of sacrificial animals, to debt financing, the recording is done simply by writing the name of the donor and what items are donated in a notebook. As well as with the reporting reported by the to minana verbally